THE IMPACT OF FISCAL POLICY IMPACT ON INCOME INEQUALITY AND ECONOMIC GROWTH: A CASE STUDY OF DISTRICT/CITY IN JAVA - Aziz, Harry Azhar; Laili, Nisful; Prihantono, Gigih (Journal of Indonesian Applied Economics, 2016)
Indonesian government has planned a policy in both accelerating the economic growth and reducing the income inequality. The improvement of income equality in Indonesia is conducted specifically through tax and transfer system. The progressive tax system is conducted to redistribute income and to reduce income inequality (measured by Gini index). The efficiency of a low tax system gave rise to suspicion that the system is not effective for reducing income inequality. This study examines the effect of fiscal policy on income ineaquality and economy growth in Java. To achieve the objective of study, the changes of macroeconomic indicators, tax system efficiency, and the changes of the income distribution is analysed using a panel data regression model. The results showed that the redistribution value of district/city is negative, indicating that the redistribution through taxes is not effective. In practice, the applicable tax system tends to widen the income inequality. The relation between equity income and economic growth show greater influence in the region with high income, whereas in regions with low income, incidence of such influence is very small indeed.Â Â